Implementasi K-Nearest Neighbor pada Decission Support System Pemilihan Satuan Pengamanan Event Perguruan Tinggi - Setiawan, Aries; Widjajanto, Budi; Kurniawan, Achmad Wahid; Budi, Setyo (Teknik Informatika Universitas Pamulang, 2020)
Routine events required by tertiary institutions require escort from selected security guards. Elections based on personal subjectivity will lead to results that are not in accordance with the purpose of the security itself. However, if the selection is based on the objectives will give results that are in accordance with professionalism. Each security unit has a different level of importance, so that at the level of security the event needs a level of professionalism in accordance with the level of importance at the college level. In detail the selection of security units on several criteria, namely event, years of service, cooperation, service, personality, skills and responsibilities. The method used in this selection process is the K-Nearest Neighbor, with the final result approval rate ofÂ 0.88%